2021
DOI: 10.3168/jds.2020-18819
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of immunomagnetic beads coupled with a rhodamine hydrazine immunosensor for the detection of Mycobacterium avium subspecies paratuberculosis in bovine feces, milk, and colostrum

Abstract: The aim of this study was to develop and evaluate a method for detecting Mycobacterium avium ssp. paratuberculosis (MAP) bacteria in bovine fecal, milk, and colostrum samples using immunomagnetic beads (IMB) and a rhodamine hydrazone immunosensor. Immunomagnetic beads were prepared by using purified antibodies from hyperimmunized sera that were coupled to Fe nanoparticles with diethylene triamine pentaacetic acid (DTPA) or ethyl (dimethyl aminopropyl) carbodiimide (EDC)-N-hydroxy succinimide (NHS) as linkers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Their main characteristics include: (i) fast separation speed, high efficiency, and good repeatability; (ii) simple operation without the need for expensive equipment; (iii) minimal impact on the biological characteristics and functions of the isolated cells; (iv) specific separation achieved by coupling specific antibodies and probes [22]. Magnetic bead-based separation has been widely used in clinical diagnosis, isolation and detection of various tumor cells, bacteria, and other microorganisms due to its high efficiency, rapidity, simplicity, non-toxicity, low cost, high separation purity, and retention of cell activity [23][24][25]. In our study, we utilized biotin-avidin coupling between antibodies and magnetic beads, resulting in strong covalent bonds [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Their main characteristics include: (i) fast separation speed, high efficiency, and good repeatability; (ii) simple operation without the need for expensive equipment; (iii) minimal impact on the biological characteristics and functions of the isolated cells; (iv) specific separation achieved by coupling specific antibodies and probes [22]. Magnetic bead-based separation has been widely used in clinical diagnosis, isolation and detection of various tumor cells, bacteria, and other microorganisms due to its high efficiency, rapidity, simplicity, non-toxicity, low cost, high separation purity, and retention of cell activity [23][24][25]. In our study, we utilized biotin-avidin coupling between antibodies and magnetic beads, resulting in strong covalent bonds [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…According to Khosravi et al (2021), 14 Fe nanoparticles were produced by the heat solvent method. Then, DTPA 200 mg was dissolved in 1 mL of DMSO; the volume of the mixture was adjusted to 5 mL using 0.1 M Tris–HCL pH 7.2; 10 μL of Triton X 100 was added to the reaction, and the pH of this mixture was adjusted to 9.6.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of quenching was used as an internal indicator to determine the amount of drug released. Khosravi et al [60] reported the fabrication of immunomagnetic nanoparticles using a rho-damine hydrazone immunosensor (see Figure 20) for separating Mycobacterium avium spp. paratuberculosis (MAP) bacteria from bovine feces, milk, and colostrum.…”
Section: Hydrazone-based Hydrogels and Particlesmentioning
confidence: 99%